Dual-task versus single-task gait rehabilitation after stroke: the protocol of the cognitive-motor synergy multicenter, randomized, controlled superiority trial (SYNCOMOT) - Sophie Tasseel-Ponche; Martine Roussel; Monica N. Toba; Thibaud Sader; Vincent Barbier; Arnaud Delafontaine; Jonathan Meynier; Carl Picard; Jean-Marc Constans; Alexis Schnitzler; Olivier Godefroy; Alain Pierre Yelnik (Trials, 2023)
Abstract Background Gait disorders and cognitive impairments are prime causes of disability and institutionalization after stroke. We hypothesized that relative to single-task gait rehabilitation (ST GR), cognitive-motor dual-task (DT) GR initiated at the subacute stage would be associated with greater improvements in ST and DT gait, balance, and cognitive performance, personal autonomy, disability, and quality of life in the short, medium and long terms after stroke. Methods This multicenter (n=12), two-arm, parallel-group, randomized (1:1), controlled clinical study is a superiority trial. With p<0.05, a power of 80%, and an expected loss to follow-up rate of 10%, the inclusion of 300 patients will be required to evidence a 0.1-m.s−1 gain in gait speed. Trial will include adult patients (18–90 years) in the subacute phase (0 to 6 months after a hemispheric stroke) and who are able to walk for 10 m (with or without a technical aid). Registered physiotherapists will deliver a standardized GR program (30 min three times a week, for 4 weeks). The GR program will comprise various DTs (phasic, executive function, praxis, memory, and spatial cognition tasks during gait) in the DT (experimental) group and gait exercises only in the ST (control) group. The primary outcome measure is gait speed 6 months after inclusion. The secondary outcomes are post-stroke impairments (National Institutes of Health Stroke Scale and the motor part of the Fugl-Meyer Assessment of the lower extremity), gait speed (10-m walking test), mobility and dynamic balance (timed up-and-go test), ST and DT cognitive function (the French adaptation of the harmonization standards neuropsychological battery, and eight cognitive-motor DTs), personal autonomy (functional independence measure), restrictions in participation (structured interview and the modified Rankin score), and health-related quality of life (on a visual analog scale). These variables will be assessed immediately after the end of the protocol (probing the short-term effect), 1 month thereafter (the medium-term effect), and 5 months thereafter (the long-term effect). Discussion The main study limitation is the open design. The trial will focus on a new GR program applicable at various stages after stroke and during neurological disease. Trial registration NCT03009773 . Registered on January 4, 2017.